Factors Associated With Decreased Accuracy of Modified Thrombolysis in Cerebral Infarct Scoring Among Neurointerventionalists During Thrombectomy. Issue 11 (9th September 2021) - Pressman, Elliot; Waqas, Muhammad; Sands, Victoria; Siddiqui, Adnan; Snyder, Kenneth; Davies, Jason; Levy, Elad; Ionita, Ciprian; Guerrero, Waldo; Ren, Zeguang; Mokin, Maxim
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The modified Thrombolysis in Cerebral Infarct (mTICI) score is used to grade angiographic outcome after endovascular thrombectomy. We sought to identify factors that decrease the accuracy of intraprocedural mTICI. Methods: We performed a 2-center retrospective cohort study comparing operator (n=6) mTICI scores to consensus scores from blinded adjudicators. Groups were also assessed by dichotomizing mTICI scores to 0–2a versus 2b–3. Results: One hundred thirty endovascular thrombectomy procedures were included. Operators and adjudicators had a pairwise agreement in 96 cases (73.8%). Krippendorff α was 0.712. Multivariate analysis showed endovascular thrombectomy overnight (odds ratio [OR]=3.84 [95% CI, 1.22–12.1]), lacking frontal (OR, 5.66 [95 CI, 1.36–23.6]), or occipital (OR, 7.18 [95 CI, 2.12–24.3]) region reperfusion, and higher operator mTICI scores (OR, 2.16 [95 CI, 1.16–4.01]) were predictive of incorrectly scoring mTICI intraprocedurally. With dichotomized mTICI scores, increasing number of passes was associated with increased risk of operator error (OR, 1.93 [95 CI, 1.22–3.05]). Conclusions: In our study, mTICI disagreement between operator and adjudicators was observed in 26.2% of cases. Interventions that took place between 22:30 and 4:00, featured frontal or occipital region nonperfusion, higher operator mTICI scores, and increased number of passes had higher odds of intraprocedural mTICI inaccuracy.